Morphological description and histological structure of olfactory organ in Rabbit(Oryctolagus cuniculus) - أشواق أحمد حسين; حسين عبد المنعم داود (Journal of Madenat Alelem University College, 2012)
Morphological description and histological structure of olfactory organ in rabbit (Oryctolagus cuniculus) have been studied from specimens collected from local markets at Bagdad city. Results of the present study showed that the olfactory organ in rabbit consist of pair of nasal chamber which located inside the nose and situated above the upper lip. The nasal cavities opened to outside through the external nares which is appears as an oval shaped opening with fleshy end at the apex of rostrum ,while they are opened to the nasopharynx region through the internal nares which are located at the upper region of soft palate. The nasal cavities are separated by the nasal septum and there are many internal and three external chonchae in each cavity. The Results of the present study revealed that the nasal cavity in rabbit is lined by two types of epithelium which are represented by the olfactory (sensory) and respiratory (non sensory) epithelium .The respiratory epithelium lines the lateral wall of the nasal cavity and covers the surface of external chonchae. It contains ciliated and non-ciliated columnar cells in addition to the goblet cells. The microscopic examination revealed that the olfactory epithelium in rabbit is a pseudostratified columnar epithelium with three types of cells :(Basal, supporting and receptor cells).The olfactory epithelium covers the upper part of nasal cavity within the internal chonchae. The lamina properia contains blood vessels, fibers and branched tubulo-alveolar glands with duct lined by simple columnar epithelium. The present study revealed that in rabbit there is vomeronasal organ which represented an accessory olfactory organ.